A quantitative assessment of the level of knowledge, attitude and practices of farmworkers regarding schistosomiasis in a rural community in South Africa - Fulufhelo Nenzhelele; Felix C. Anyanwu; Mamabolo Ramoteme; Jabu Mabunda; Akinsola Henry; Kyei Kwabena (AOSIS, 2020)
Background: Schistosomiasis is associated with agriculture and water development schemes, and farmworkers are particularly vulnerable to this disease because of their regular contact with water. Aim: To determine the level of knowledge, attitude and practices (KAP) of farmworkers regarding schistosomiasis. Setting: This study was conducted in Vuvha, a rural community under Makhado municipality, Vhembe district, Limpopo Province, South Africa. Methods: A quantitative, cross-sectional design was used. A self-administered questionnaire was used for data collection, and data were analysed using descriptive and inferential statistical techniques. Results: The majority were knowledgeable about the cause of schistosomiasis (84.3%), knew the mode of transmission of the disease (90.2%). However, about half of the participants knew the symptoms of schistosomiasis. Sixty-eight (33.4%) believed that schistosomiasis was not a problem in their community. The majority (77.9%) agreed that it was abnormal to pass blood in urine, while 85.8% agreed that medical consultation was the right thing to do when symptoms are observed. Fifty-five participants (27.0%) reported ever passing bloody urine. Among those who passed bloody urine, 43 (78.2%) consulted a doctor. Fifty-two (26.0%) participants reported ever being treated for schistosomiasis. Conclusion: The level of knowledge about the cause of schistosomiasis is high among the participants; similarly, there are positive attitudes and good practices shown in this study, but there are some gaps that need to be addressed. Efforts should be made to continue to educate farmworkers because they are at an increased risk for contracting schistosomiasis.